Neurofibroma of lumbosacral region: a case report - ., Elfiah; Asmiragani, Syaifullah (International Journal of Research in Medical Sciences, 2019)
Neurofibromas are benign tumors of the peripheral nerve sheath. Spinal neurofibroma often asymptomatic. Symptoms may present include sensory changes. Neurofibroma mostly encountered cervical cord, difficult to distinguish from schwannomas. This slow growing tumor remodel the bone resulting pedicle thinning and posterior vertebral body scalloping. MRI shows hyperintense rim. Although this highly suggestive neurofibroma, occasionally also seen in schwannoma and malignant PNST. Treatment choice for symptomatic lesions is surgery. We are reporting a case of neurofibroma in the 5th lumbar and 1st sacral region.